Use of overactive bladder anticholinergic medications associated with falls leading to emergency department visits: results from the ADRED study - Just, Katja S.; Schultze, Karen A.; Dormann, Harald; Seufferlein, Thomas; Gräff, Ingo; Scholl, Catharina; Schwab, Matthias; Stingl, Julia C. (European Journal of Clinical Pharmacology, 2023)
Purpose: Drug intake might be a modifiable factor for the individual fall-risk of older adults, and anticholinergic properties of drugs need to be considered. This study is aimed at analyzing the association of older adults’ individual anticholinergic load with particular focus on use of overactive bladder anticholinergic medications with falls in multi-medicated patients. Materials and Methods: Cases of the prospective, observational, multi-center study on adverse drug reactions leading to emergency departments (ADRED study) between 2015 and 2018 in Germany were analyzed comparing the exposure of overactive bladder anticholinergic medications on the chance to present with a fall with patients without exposure. Logistic regression analysis was used adjusting for pre-existing conditions, drug exposure, and the individual anticholinergic burden by drug use. To this end, a combination of seven expert-based anticholinergic rating scales was used. Results: The anticholinergic burden was higher in patients with overactive bladder anticholinergic medications (median 2 [1; 3]) compared to not taking drugs of interest. Presenting with a fall was associated with overactive bladder anticholinergic medications (odds ratio (OR) 2.34 [95% confidence interval 1.14–4.82]). The use of fall-risk increasing drugs was likewise associated (OR 2.30 [1.32–4.00]). The anticholinergic burden itself seemed not to be associated with falls (OR 1.01 [0.90–1.12]). Conclusions: Although falls occur multifactorial in older adults and confounding by indication cannot be ruled out, the indication for a drug treatment should be decided with caution when other, non-pharmacological treatment options have been tried. German clinical trial register: DRKS-ID: DRKS00008979, registration date 01/11/2017.
CRIS-Team Scopus Importer:2025-02-03
Keywords: Adverse drug reaction; Anticholinergic; Fall-risk increasing drugs; Multi-medication; Older adults; Overactive bladder anticholinergic medications; Urologicals